Rejection of Funeral for Covid-19 Patients: Indonesian Legal Perspective - Fifik Wiryani; Setyo Sugiharto; M Nasser; Mokhammad Najih (Muhammadiyah University Press, 2020)
Purpose of the study:This study aims to solve the problem of citizens who refuse funerals/bodies of Covid-19 patients.Methodology The method used in this study is a normative juridical method using statutory, conceptual and case approaches.Results This study found that it is necessary to socialize, educate and communicate to the citizens that the Covid-19 bodies have gone through stages in accordance with medical protocol and WHO in the treatment/repatriation of bodies so that there should be no need for excessive fear while if residents refuse funerals Covid-19 patients' bodies there are sanctions including moral sanctions, fines and criminal confinement.Applications of this studyThis research can be used by academics and practitioners in health law, so that they can create an instrument to socialize the acceptance of Covid-19's bodies in the community.Novelty/ Originality of this study The bodies of Covid-19 patients have been carried out the repatriation (management) of the bodies in accordance with the standards of who's health protocol (World Health Organization), namely the bodies wrapped in three layers of shrouds and linen and two layers of body bags. then the body in Tayyamum using dust, the body and then placed into the coffin that was placed typical and has been sprayed disinfectant liquid, then the coffin closed tightly using silicone glue and then given nails on each side of the coffin.